68 Administration of artemisinin analogue SM934 ameliorates disease manifestation in lupus-prone mice via restoring immune homeostasis. (April 2019) - Lin, Zemin; Zuo, Jianping; He, Shijun; Tang, Wei
Abstract : Background: Artemisinin and its derivatives were reported to possess strong regulatory effects on inflammation and autoimmune diseases. This study was designed to examine the therapeutic effects and underlying mechanisms of SM934, a water-soluble artemisinin analogue, on lupus-prone mice. Methods: For MRL/lpr mice: In vivo, the preventative or therapeutic effects of SM934 in MRL/lpr mice were investigated. Ex vivo, the mechanisms of treatment were explored according to the immunologic correlates of disease. Impacts of SM934 on Toll-like receptor (TLR)-triggered B cell responses were evaluated. In vitro, the effects of SM934 on the activation and differentiation of CD4 +T cells were examined. For NZB/W F1 mice: In vivo, the lupus-prone mice were treated with SM934 for 3 or 6 months respectively to investigate the effect on clinical manifestations and immunological correlates. To further explore the mechanisms of SM934, ovalbumin (OVA)-immunized or interferon (IFN)--elicited C57BL/6 mice were used. Results: In vivo, SM934 treatment significantly prolonged the life-span of MRL/lpr mice, ameliorated the lymphadenopathy, decreased the levels of serum anti-nuclear antibodies (ANAs) and the pathogenic cytokines IFN-, IL-6, IL-10 and IL-21, and reduced the proportion of double negative T cells. Treatment with SM934 significantly delayed the progression of glomerulonephritis and improved the survival of NZB/W F1 mice. Clinical improvement was accompanied with decreased anti-dsDNA Abs and serum interleukin IL-17. In addition, SM934 treatment promoted the IL-10 production from macrophages of NZB/W F1 mice, OVA-immunized C57BL/6 mice and IFN--elicited C57BL/6 mice. Ex vivo, SM934 treatment elevated the percentage of Treg cells, inhibited the development of Th1 and Th17 cells. Moreover, SM934 suppressed the TLR-triggered activation and proliferation of B cells. In vitro, SM934 inhibited the differentiation of Th1 and Th17 cells as well as TLR-associated B-cell activation and plasma cell differentiation. SM934 enhanced IL-10 production from primary macrophages stimulated with IFN-. Conclusions: Taken together, these results demonstrated that the artemisinin analogue SM934 exerted significant therapeutic benefits in lupus-prone mice, by inhibiting both the pathogenic helper T cell development and responses, enhancing anti-inflammatory cytokine IL-10 production and suppressing plasma cell formation. These properties of SM934 might contributed to the restoration of the immune homeostasis in lupus-susceptible mice, and thus cast a light on a novel strategy for lupus treatment. Funding Source(s): National Science Fair Committee (NSFC), China (No. 81273524, 81322049), National Science and Technology Major Project New Drug Creation and Manufacturing Program, China (2014Z × 09101002) and National Key Basic Research Programme (973 Programme, 2014CB541906). Artemisinin analogue SM934 treatment restore immune homeostasis in lupus-prone mice